THE IMAGES OF EXTRAGALACTIC RADIO SOURCES IN THE DIFFUSION MODEL - Kolesnikov, F. M.; Kontorovich, V. M. (Одеські астрономічні публікації, 2017)
The distribution of the spectral index and radio lobes' isophots were derived by numerical methods in the diffusion model of extragalactic radio sources. The kinetic equation for the distribution function of relativistic electrons is considered. Regions of electron injection, associated with hot spots, are considered as moving. Velocities of hot spots and the diffusion velocity of electrons determined the correlation of transverse and longitudinal lobes' sizes. Observed changes of lobes at various frequencies accord with the diffusion model. The reabsorption in the lobes leads to the asymmetry of them, depending on source's rotation relatively to the line of sight.